2008 International Conference on Nanoscience and Nanotechnology 2008
DOI: 10.1109/iconn.2008.4639258
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of the anticancer drug cisplatin into nanotubes

Abstract: One important application of nanotechnology is that of drug delivery, and in particular the targeted delivery of drugs using nanotubes. A proper understanding of the encapsulation behavior of drug molecules into nanotubes is vital for the development of nanoscale drug delivery vehicles. Furthermore, there are many other materials which may form single-walled nanotubes, such as carbon, boron carbide, boron nitride and silicon, and it is also important to understand their advantages and disadvantages. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…For this purpose, we performed the following calculations. Hilder and Hill [13] expressed the Lennard-Jones potential as U = -A/r 6 ? B/r 12 .…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we performed the following calculations. Hilder and Hill [13] expressed the Lennard-Jones potential as U = -A/r 6 ? B/r 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Various purification processes have been reported to separate metallic and semiconducting SWCNT mixtures, such as electrophoresis, centrifugation, chromatography, and solubilisation [55][56][57]. However, purification of semiconducting SWNTs can add considerable time and resources to the production process [56], and as CNT-FET device for biosensing using antibody receptors (reproduced with permission from [22]); (c) Electrochemical sensor for glucose consisting of an Au electrode bonded to a CNT-GO x which detects redox reactions between FAD and glucose (reproduced with permission from [51]); (d) "basket-like" periodic MWNT lattices into which mice fibroblast is to be implanted (reproduced with permission from [52]); (e) alginate-polylysinealginate microcapsule destruction by the photoacoustic effect by folate acid-functionalized SWNTs inside the cells (reproduced with permission from [53]); (f) loading and unloading of molecules inside CNTs for drug delivery; drugs are released when a CNT is uncapped within the cytoplasm of the cell (reproduced with permission from [54]).…”
Section: Carbon Nanotubes For Biosensing the Incorporation Ofmentioning
confidence: 99%
“…Secondly, each CNT can be functionalized to detect and interact with a single cell, improving the delivery efficiency and reducing the drug dosage [17,116]. It has been demonstrated that 5 million species can be bonded to an 80 nm long CNT [54]. The combination of size and ease of functionalization allows CNT to deliver drugs to cells, such as neurons and cardiomyocytes, which are difficult to reach by traditional drug-delivery methods [117].…”
Section: Carbon Nanotubes In Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the changes occurring in the molecular geometrical structure and the thermodynamic stability when it is confined inside the hollow space of capped nanotubes SWCNT(12,0), SWCNT (14,0), and SWCNT(16,0) by considering mainly the van der Waals interaction have been investigated. This study is performed to predict the encapsulation of this molecule into carbon nanotubes; the long-term objective is to perform a targeted delivery of this molecule in cancer cells following the model proposed by Hilder et al [29]. In this study, the molecular structure analysis of the studied molecule has been performed in gas phase and aqueous solution by a DFT method and inside the nanotube cavity by an ONIOM(DFT:MM) method.…”
Section: Introductionmentioning
confidence: 99%